Profitability in View of Working Capital Efficiency, Liquidity and Solvency: Does Company Size Moderate? - Eka Anggrahini, Sapna; Harjito, Yunus; Rahman Siddiq, Faiz; Nursiva Yuniar, Anastasya (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to analyze the influence of working capital efficiency, liquidity and solvency on company profitability, moderated by company size. The population of this research is cosmetic companies registered on the Indonesian Stock Exchange (BEI) for the 2015-2022 period. The sample for this research consisted of 48 samples obtained from 6 companies over 8 years using the purposive sampling method. The analysis technique used focuses on multiple regression analysis and moderated regression analysis using the SPSS application. The results of this research show that working capital efficiency has a significant negative influence on profitability, while liquidity and solvency have no influence on profitability. Furthermore, the results of the moderation test showed that the company size variable was able to moderate the relationship between working capital efficiency and profitability.